Eco-friendly synthesis of silver nanoparticles using Withania somnifera root extract: characterization, phytochemical profiling, and evaluation of antimicrobial activity - Thapa, Ratna Bahadur; Ojha, Shankar Datt; Dhungana, Sujan; Tiwari, Laxmi; Khadka, Devendra; Poudel, Milan Babu; Pokhrel, Megh Raj; Baral, Janaki; Poudel, Bhoj Raj (BIBECHANA, 2025)
Silver nanoparticles (Ag NPs) were synthesized using a green chemistry approach, utilizing Withania somnifera (Ashwagandha) root extract, whose phytochemicals acted as eco-friendly, non-toxic reducing agents. The synthesized AgNPs was characterized using X-ray diffraction (XRD), UV-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR),  scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS).  XRD analysis confirmed the crystal structure of the Ag NPs and estimated their size to be 10 nm. UV-visible spectroscopy showed a characteristic absorption peak, confirming the formation of AgNPs. FTIR analysis identified functional groups associated with the phytochemicals in the root extract, which may contribute to nanoparticle stabilization. SEM images revealed the spherical morphology of the Ag NPs, while EDS analysis confirmed the presence of silver in the synthesized nanoparticles. The phytochemical examination of Ashwagandha found secondary metabolites, including phenolic, alkaloid, and flavonoid compounds. The synthesized Ag NPs were assessed for their antimicrobial activity against Staphylococcus aureus, Escherichia coli, and Candida albicans, demonstrating significant efficacy markedly against Gram-positive bacteria. This finding highlights the role of Ashwagandha-mediated Ag NPs in sustainable NP formation and antimicrobial applications.